2002
DOI: 10.2751/jcac.3.48
|View full text |Cite
|
Sign up to set email alerts
|

Extended CAST Coding Method for Exact Search of Stereochemical Structures

Abstract: Accurate recognition of differences and similarities in stereochemical structures is achieved by extended CAST (CAnonical-representation of STereochemistry) coding method. Using the CAST notations, complete search of partial structures as well as whole structures by matching with the query in any level from a specific atom considering planar, configurational, and conformational information has been achieved. Differences and similarities of stereochemistry in four aldopentoses of D-xylose, D-ribose, D-arabinose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In previous papers, one of us developed a new stereochemical coding method, CAST (CAnonical representation of STereochemistry) and successfully applied it to a database-oriented 13 C NMR chemical shift prediction system, called CAST/CNMR . In the course of studies applying CAST/CNMR to terphenyls, we found that 13 C NMR data of the terminal aromatic rings of 1 were similar to those of ganbajunin C isolated from edible Chinese mushroom, Thelephora ganbajun (Figure ) and felt that the proposed structure 14 was quite strange because two model compounds ( 15 and 16 18 ) exhibited clearly different 13 C NMR spectra (Table ).…”
mentioning
confidence: 94%
“…In previous papers, one of us developed a new stereochemical coding method, CAST (CAnonical representation of STereochemistry) and successfully applied it to a database-oriented 13 C NMR chemical shift prediction system, called CAST/CNMR . In the course of studies applying CAST/CNMR to terphenyls, we found that 13 C NMR data of the terminal aromatic rings of 1 were similar to those of ganbajunin C isolated from edible Chinese mushroom, Thelephora ganbajun (Figure ) and felt that the proposed structure 14 was quite strange because two model compounds ( 15 and 16 18 ) exhibited clearly different 13 C NMR spectra (Table ).…”
mentioning
confidence: 94%
“…and H.S.) developed a new stereochemical coding method, CAST (CAnonical-representation of STereochemistry) [15][16][17] and successfully applied it to a database-oriented 13 C NMR chemical shift prediction system, called CAST/CNMR. [18][19][20] In the course of studies applying CAST/CNMR to cycloart-23-en-25-ol derivatives, we could not find reliable 13 stereochemistry.…”
mentioning
confidence: 99%
“…and H.S.) developed a new stereochemical coding method, CAST (CAnonical-representation of STereochemistry) and successfully applied it to a database-oriented 13 C NMR chemical shift prediction system, called CAST/CNMR. In the course of studies applying CAST/CNMR to cycloart-23-en-25-ol derivatives, we could not find reliable 13 C NMR data of compounds with the 2-methyl-3-penten-2-ol moiety that possesses Z stereochemistry. Total synthesis of 1 and 2 also has not been reported. Therefore, we planned to prepare authentic samples to add into the database of CAST/CNMR.…”
mentioning
confidence: 99%
“…Thus, the core part of this study is to develop an ecient algorithm to solve this maximization problem eq. (12).…”
Section: Development Of G-rmsd Methodsmentioning
confidence: 99%